الصور البلاغية في كتاب التاريخ الأدبي للعصر العثماني والحديث للمرحلة الثانوية العالية الدينية الماليزية STAM دراسة وصفية وتحليلية - Nuraznan Jaafar
This study is based on methodology used in the writing of a Nusus Al-Arabiah in text books of Tarikh Al-Adabi produced by the Education Ministry (MOE) for students of Sijil Tinggi Agama Malaysia (STAM). However in Malaysia, it is less suitable and cannot be understood by the majority of STAM students. In the end students only memorize verses of poetry without being able to understand the texts they are studying. There are three pieces of poetry: "Toifu Samiroh" by Mahmud Sami Al-Barudi (1838 H), the poem "Al-Mawakib" by Jibron Kholil Jibron (1883 H) and the poem "Nahju Al-Burdah" by Ahmad Shauki (1868 H). Therefore, the researcher studied the verses of the poems mentioned base on Balaghah (Rethoric) which is specific to the Bayan branch of knowledge without touching on Ma’ani and Badi’. This was accomplished by producing the artistic imagery of Bayan which can be found in all three poems. Descriptive and analysis of the texts of the poem was determined by referring to the collection of poems by the three poets. The researcher used Al-Arabi dictionary by Ibn Manzur which offers various meanings to each word as well as Al-Miftah dictionary by Muhamad Khairi Zainudin to identify the meanings of the Arabic terms in Malay. The findings showed that there are a lot of artistic imageries of Bayan from the three poems that cannot be clearly defined. In addition, necessary amendments in writing method of Nusus Al-Arabiah which was written generally based on Bayan was also highlighted because it can help bring additional understanding to the STAM students.